2019
DOI: 10.3390/ani9070470
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Single Shot Multibox Detector Method Applied in Body Condition Score for Dairy Cows

Abstract: Body condition scores (BCS) is an important parameter, which is in high correlation with the health status of a dairy cow, metabolic disorder and milk composition during the production period. To evaluate BCS, the traditional methods rely on veterinary experts or skilled staff to look at a cow and touch it. These methods have low efficiency especially on large-scale farms. Computer vision methods are widely used but there are some improvements to increase BCS accuracy. In this study, a low cost BCS evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…Body condition is a significant welfare and herd management indicator. Body condition is in high correlation with the health and metabolic status of the dairy cow and also with milk composition during lactation [ 105 ]. Body condition assessment is an indirect appraisal of the level of body reserves, and deviations reveal aggregate variation in energy balance [ 106 , 107 ].…”
Section: Welfare Of Dairy Cows and Precision Livestock Farmingmentioning
confidence: 99%
“…Body condition is a significant welfare and herd management indicator. Body condition is in high correlation with the health and metabolic status of the dairy cow and also with milk composition during lactation [ 105 ]. Body condition assessment is an indirect appraisal of the level of body reserves, and deviations reveal aggregate variation in energy balance [ 106 , 107 ].…”
Section: Welfare Of Dairy Cows and Precision Livestock Farmingmentioning
confidence: 99%
“…So when there are some limitations and speed constraints, the more important metrics should be taken into account and compared to help to choose the right method [79]. However, there are studies that improve the accuracy of detection and speed of processing to make these suitable for real-time applications [50,52,103].…”
Section: Discussionmentioning
confidence: 99%
“…Kvam and Kongsro [49] proposed a method for estimating the IMF on ultrasound images. A noninvasive in vivo method, constructed using deep CNNs, by (Huang et al [50] and Yukun et al [51] provided a lowcost method based on machine vision and deep learning for evaluation of body condition scores. Zhang et al [52] proposed a real-time sow behavior detection algorithm based on deep learning.…”
Section: Precision Livestock Farmingmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only that, BCS is also important in farm management [ 9 ]. It was found that BCS at calving and its changes throughout lactation affect the health and fertility of high producing dairy cows [ 10 ]. Cow BCS monitoring is important because it is a measure for the fat reserves of a cow, also suitable in the assessment of feeding management.…”
Section: Introductionmentioning
confidence: 99%